Efcacy of Low-Intensity Aerobic Exercise and Aerobic Combined with Resistance Exercise on Pain, Respiratory Function, Fatigue and Qualityof Life in Nursing Patients - Šarūnas Kvietkauskas; Vilma Juodžbalienė (Lithuanian Sports University, 2023)
Background. In older people with multiple comorbidities, quality of life declines due to physical deterioration, which may also contribute to psychological deterioration (Nóbrega et al., 2009; Subramaniam et al., 2019). In such cases, it is important to ensure adequate physical activity, as it can improve their physical and psychological condition (Bricca et al., 2020). Physical activity including aerobic exercises, resistance exercises, and stretching exercises can improve the quality of life in elderly (López-Torres, 2019), but it remains unclear which physical exercises are more effective. The aim. To determine which of the physiotherapy programs - low-intensity aerobic exercises or combined aerobic and resistance exercises - are more effective in reducing pain and fatigue of nursing patients, improving respiratory indicators and quality of life. Methods. 20 patients 74.85±5.4 years of age participated in the study. Subjects were randomly divided into two groups: MIAP group - applied low-intensity aerobic exercise, APP group - aerobic and resistance exercise. Perceived pain was assessed using numerical pain scale (SAS). Respiratory function indicators were evaluated by spirometry. The multidimensional fatigue inventory (MFI-20L) assessed general, physical and mental fatigue, decreased activity and motivation. The SF-36 questionnaire was used to assess the quality of life. Results. Applying the MIAP and APP programs was significantly reduced pain, physical fatigue, improved quality of life related to physical and mental health, and respiratory indicators (p<0.05). Conclusions. A low-intensity aerobic exercise program was more effective in reducing fatigue, while an aerobic and resistance exercise program was more effective in improving respiratory function. Both programs were effective in improving mental and physical health-related quality of life and reducing pain. Keywords: physiotherapy, quality of life, pain, respiratory function, fatigue.